Application of Photoacoustic Imaging for Pneumonia Detection - Maqfiroh, Caesarany; Widyaningrum, Rini; Anas, Ahmad Mujtahid; Mitrayana, Mitrayana (UI Scholars Hub, 2023)
We used photoacoustic imaging (PAI) to visualize and compare acoustic intensity levels in pneumonia-affected and healthy chicken lungs. After histological confirmation of pneumonia, the samples were scanned and subjected to a 532-nm diode laser in a photoacoustic imaging system. The acoustic intensity level of pneumonia-affected tissue was examined and compared with that of healthy lung samples. The optimum laser frequency and duty cycle for imaging the samples were 17 kHz and 30%, respectively. The acoustic intensity levels of pneumonia-affected tissue and healthy lungs were −82.5 ± 1.8 dB and −79.9 ± 1.3 dB, respectively. We found that a simple PAI device consisting of a diode laser and condenser microphone could distinguish between pneumonia-affected and healthy lungs. Pneumonia-affected lungs produced less acoustic intensity than that healthy lungs, as supported by histological studies.